International electronics directory '90 : the guide to European manufacturers, agents and applications. - Wedgwood, C. G. (Elsevier Advanced Technology, 1990)
International Electronics Directory '90: The Guide to European Manufacturers, Agents and Applications, Part 2 focuses on information on manufacturers, agents, and applications. The book first presents a list of companies and abbreviations. The text then underscores a classified list of products and services. This includes electronics for office administration, aerospace industry, security and alarm systems, automobile industry, and banking; computers and ancillary equipment; consumer electronics; and electronics for environmental monitoring. Other products and services mentioned include electr.